2008
DOI: 10.1111/j.1365-2141.2008.07065.x
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for Ikaros regulation of human globin gene switching

Abstract: SummaryThe human b globin locus consists of an upstream LCR and functional genes arranged sequentially in the order of their expression during development: 5¢-HBE1, HBG2, HBG1, HBD, HBB-3¢. Haemoglobin switching entails the successive recruitment of these genes into an active chromatin hub (ACH). Here we show that the transcription factor Ikaros plays a major role in the formation of the b-globin ACH, and in haemoglobin switching. In Plastic mice, where the DNA-binding region of Ikaros is disrupted by a point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Previous studies have shown that Ikaros binds the hu␤-globin locus in vitro and, when overexpressed in K562 erythroleukemia cells, which express hu␥-but not hu␤-globin upon induction, Ikaros-1 binds to ␤LCR HS3 (20,35). However, the physiological role of Ikaros and the molecular mechanisms modulated by Ikaros during globin switching remain to be defined.…”
Section: Ikaros Binds To the Hu␤-globin Locus In Erythroid Cells It mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Ikaros binds the hu␤-globin locus in vitro and, when overexpressed in K562 erythroleukemia cells, which express hu␥-but not hu␤-globin upon induction, Ikaros-1 binds to ␤LCR HS3 (20,35). However, the physiological role of Ikaros and the molecular mechanisms modulated by Ikaros during globin switching remain to be defined.…”
Section: Ikaros Binds To the Hu␤-globin Locus In Erythroid Cells It mentioning
confidence: 99%
“…In Ik null mice carrying a human minilocus, ␥-to ␤-globin switching is delayed (26,35), B and T lymphopoiesis and hematopoietic stem cell (HSC) activities are severely affected, and reduction in HSCs leads to decreased BFU-E and CFU-E activities (33). Fetal-to-adult globin switching is also delayed in Ikaros Plastic mice harboring a point mutation in the third zinc finger of Ikaros, which selectively disrupts DNA binding (20,39)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mice harboring a point mutation in the third zinc finger of Ikaros (the resulting protein retains its ability to dimerize with isoforms and family members, but is defective in DNA binding) die of anemia in late gestation with a much more severe phenotype [78]. n these mice, a marked downmodulation of β-globin and upregulation of γ-globin expression was observed; furthermore, chromatin conformation capture data demonstrated that Ikaros facilitates longdistance DNA looping between the LCR and a region upstream of δ-globin gene [79].…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 99%
“…Depending on the competitive nature of the surrounding chromatin, additional cis regulatory elements, such as the Enh and F silencers, may have evolved to stabilize the enhancerpromoter interactions in the ACH and maintain the required expression level at a particular developmental stage. The transcriptional outcome of an ACH critically depends on the productive interaction between cis regulatory elements and specific developmental transcription factors, such as Ikaros and its family member Eos, which seem to participate in the regulation of hemoglobin switching by facilitating the DNA looping between the LCR and the upstream region of the δ-globin gene (54). Interestingly, the transcriptional pattern of globin gene switching seems to correlate with the switching of interactions of the individual globin genes with this spatial cluster (55).…”
Section: O V E M B E R -D E C E M B E R 2 0 0 9 T W O S I L E N C E Rmentioning
confidence: 99%